Development of Basic Physics Experimental Props 1 on Fluid Viscosity Material - Yunita Rahmani (IJOEM: Indonesian Journal of E-learning and Multimedia, 2022)
This research objectives were to Describe students' perception of the readability test of arduino-based basic physics experiment props on fluid viscosity material. The method used in this research is the Research and Development (R&D) method with ADDIE development model. Products are made using Arduino Uno and Arduino IDE software with C++ programming language. The data samples used in this study were 42 students of JPMIPA FKIP Unib (Physics Education, Chemical Education, Biology Education and Science Education). The instruments used in this student perception questionnaires. The student perception was interpreted by Likert Scale. Student perception was reviewed from 7 aspects, namely the efficiency aspects of the tool, the association with the lecture material, containing the value of education, tool durability, aesthetics, technical components and tool safety. The results obtained from this study showed that the props developed fall into the category of is the best with an average score of 87%